Effects of Development Assistance for Health in Developing Countries - MONGBET Zounkifirou; TOURERE Zenabou (International Journal of Management, Accounting and Economics, 2021)
This article assesses the effects of international aid on the health sector in developing countries. We use estimation techniques such as Ordinary Least Squares (OLS), instrumental variables with fixed effects, and the dynamic panel approach. Using the data from various sources over the period 1990 to 2017 covering 126 developing countries, the initial results show that health aid contributes effectively and significantly to improved health outcomes in the developing countries at 1 and 5% of the significance thresholds. These results give the picture that the mobilization of the international community in favour of the health sector in the context of the MDGs through health aid has been more effective in achieving certain health goals from the 2000s onwards than before the Millennium Declaration. This study shows that it is in the interest of development partners, particularly those in the health sector, to significantly improve the survival and health of the populations of developing countries through health aid. It is recommended that development assistance policies be designed to take into consideration the existing institutional framework and how these resource flows interfere with, and therefore change, the incentive structure of recipient countries. The transfer of resources in the form of health aid to meet current needs must be complemented by other additional actions, such as education campaigns and infrastructure improvements, in order to achieve long-term improvement.